2021
DOI: 10.1097/md.0000000000024246
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of Shexiang Baoxin Pill combined with Western medicine in the treatment of acute myocardial infarction

Abstract: Background: The morbidity and mortality of acute myocardial infarction are on the rise, and the efficacy of conventional treatment is limited. Shexiang Baoxin Pill is a kind of proprietary Chinese medicine, which has been widely used in the treatment of acute myocardial infarction in China, and has certain advantages. At present, there is a lack of strict randomized controlled trials to verify the efficacy and safety of Shexiang Baoxin Pill combined with Western medicine in the treatment of acute m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…Due to the inadequacy of the total sample size and the existence in some studies of a greater number of adverse reactions in the intervention group; however, we still need to be cautious about the outcome of the drug safety analysis. Nevertheless, it is encouraging to see that in recent years, a growing number of studies have shown the clinical safety of proprietary Chinese medicines [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Due to the inadequacy of the total sample size and the existence in some studies of a greater number of adverse reactions in the intervention group; however, we still need to be cautious about the outcome of the drug safety analysis. Nevertheless, it is encouraging to see that in recent years, a growing number of studies have shown the clinical safety of proprietary Chinese medicines [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nine RCTs [ 27 – 29 , 31 – 33 , 35 , 37 , 40 ] reporting a clinical efficacy rate were pooled. Among the subgroup analysis ( Figure 2 ), SBP plus RT showed a better clinical efficacy rate than RT alone (RR = 1.15, 95% CI [1.06, 1.25], p < 0.05) with low heterogeneity ( Q (6) = 8.17, p = 0.23, I 2 = 35.00%).…”
Section: Resultsmentioning
confidence: 99%
“…Seven RCTs [ 26 , 30 , 32 , 33 , 35 , 39 , 41 ] reported recurrent AMI, and nine RCTs [ 24 , 26 – 28 , 30 – 33 , 35 ] reported complication cases. SBP adjunctive to RT significantly reduced the AMI recurrent rate than RT alone (RR = 0.30, 95% CI [0.15, 0.59], p < 0.05; Q (4) = 1.45, p = 0.84, I 2 = 0, low heterogeneity), but SBP adjunctive to RT plus PCI did not present significant difference (RR = 0.64, 95% CI [0.20, 2.09], p > 0.05; Q (1) = 0.76, p = 0.38, I 2 = 0, low heterogeneity) ( Figure 6(a) ).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, following screening more than 100 kinds of clinical commonly used Chinese medicines, Styrax is found with the most potent CYP3A4 inhibitory effect (almost completely inhibit CYP3A4 at 100 μg/ml). Considering that Styrax and Styrax-related herbal products are frequently used in combination with a panel of marketed cardiovascular drugs (such as warfarin, digoxin and simvastatin) to treat cardiovascular diseases ( Zhu, 2009 ; Tao et al, 2016 ; Yang et al, 2021 ). It is well-known that Styrax/Styrax-related herbal products are often taken orally for the treatment of human diseases, while a number of studies have reported that the local distribution of herbal constituents in the intestine is much higher than that in the liver ( Lai et al, 2009 ; Wang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, Styrax is often used as a key material for preparing some marketed herbal products (such as Suhexiang Pill, Shexiang Baoxin Pill, Subing Dropping Pill, Guanxin Suhe Pill, Shixiang fansheng Pill), owing to the high safety profiles and beneficial effects of this herb in preventing and treating cardiovascular diseases ( Bian and Zhang, 2016 ; Guo et al, 2021 ). In Asia countries, Styrax and Styrax-related herbal products are frequently used in combination with a panel of marketed cardiovascular drugs (such as warfarin, digoxin and simvastatin) to treat cardiovascular diseases ( Zhu, 2009 ; Tao et al, 2016 ; Yang et al, 2021 ). As an important ester spice, Styrax is also used for making a variety of foods ( Yu, 2021 ).…”
Section: Introductionmentioning
confidence: 99%